Profiling for CA condensates - Jackson, G. L. (Melbourne : C.S.I.R.O., Central Information Library and Editorial Section, 1975)
Procedure for constructing search profile of CA CONDENSATES data base.
Cover title.
Processed.
Keywords: Documents on chemistry. Information retrieval services using digital computer systems. Machine-readable files: Chemical abstracts condensates data base. SDI services. User profiles. Manuals; Chemical abstracts condensates -- Handbooks, manuals, etc; Australia